Characterization of calcium phosphate coating produced by biomimetic method - Escada, Ana Lúcia do Amaral [UNESP]; Machado, João Paulo Barros; Claro, Ana Paula Rosifini Alves [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2015)
Titanium and its alloys have been used in dentistry to due their excellent corrosion resistance and biocompatibility. However, titanium coating is bioinert material and it cannot chemically bond to bone tissue. The purpose of this work was evaluating the bioactivity of Ti-7,5Mo alloy after chemical treatment using H2SO4/H2O2 and soaking in SBF. Samples were chemically treated at room temperature for 4 h with a solution consisting of equal volumes of concentrated H2SO4 (200 ml) and 30% aqueous solution H2O2 (200 ml). The oxidized samples were rinsed with distilled water and were heat treated at 600 degrees C for 1h in a electrical furnace in air. Then, all samples were immersed in SBF (Simulated Body Fluid) for 7 and 14 days to form a calcium phosphate (Ca/P) coating on the surface. Surfaces were characterized by using SEM, AFM and contact angle. The results indicated that calcium phosphate (Ca/P) was formed on surface of Ti-7.5Mo experimental alloy.
Keywords: Titanium alloys; Chemical treatment; Calcium phosphate